Exploring Instructional Leadership Practices in Institutional Schools of Kathmandu: A Narrative Inquiry - Subash Shrestha (The Open University of Sri Lanka, 2021)
Principals of schools are more focused on managerial work rather than supporting teaching and learning in the school. As a result, they spend most of their time behind the desk and in work pertaining to documentation. Principals are guided by the principles of achieving good grades in examinations. They tend to be more focused on rote learning rather than knowledge and skills-based learning that add value to the lives of students. However, the instructional leadership advocates that the principal should be able to create school cultures that encourage students' progress by ensuring teachers' accountability. Thus, the main aim of the paper is to explore perception and practices of principals on their instructional leadership in addressing the skills required for the 21st century. This research makes use of applied narrative approach to explore the perceptions and practices. For this purpose, this study undertook in-depth interviews with two principals from different schools of the Kathmandu valley. The findings of the study revealed that setting direction, focusing in curriculum and monitoring the learners' progress are the perception and practices of instructional leadership.